2021
DOI: 10.1038/s41467-020-20605-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-related and disease locus-specific mechanisms contribute to early remodelling of chromatin structure in Huntington’s disease mice

Abstract: Temporal dynamics and mechanisms underlying epigenetic changes in Huntington’s disease (HD), a neurodegenerative disease primarily affecting the striatum, remain unclear. Using a slowly progressing knockin mouse model, we profile the HD striatal chromatin landscape at two early disease stages. Data integration with cell type-specific striatal enhancer and transcriptomic databases demonstrates acceleration of age-related epigenetic remodelling and transcriptional changes at neuronal- and glial-specific genes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 85 publications
2
12
0
Order By: Relevance
“…Epigenetic modifications, including DNA and histone modifications have also been shown to play a crucial role in the regulation of NSC fate (Yao et al, 2016) with histone demethylation and acetylation being the main modifications promoting NSC proliferation and self-renewal and methyl-CpG binding protein 2 (MECP2)-mediated histone methylation promoting terminal neuronal differentiation and synaptogenesis (Niklison-Chirou et al, 2020). Histone methylation has been shown to influence Notch1 (Zhang et al, 2015) and Huntingtin expression (Irmak et al, 2018;Lu et al, 2020;Alcalá-Vida et al, 2021). Histone acetylases and deacetylase also regulate proper NSC function through huntingtin expression regulation (Yildirim et al, 2019).…”
Section: Mitochondrial Physiology Autophagy and Epigenetics Interplay...mentioning
confidence: 99%
“…Epigenetic modifications, including DNA and histone modifications have also been shown to play a crucial role in the regulation of NSC fate (Yao et al, 2016) with histone demethylation and acetylation being the main modifications promoting NSC proliferation and self-renewal and methyl-CpG binding protein 2 (MECP2)-mediated histone methylation promoting terminal neuronal differentiation and synaptogenesis (Niklison-Chirou et al, 2020). Histone methylation has been shown to influence Notch1 (Zhang et al, 2015) and Huntingtin expression (Irmak et al, 2018;Lu et al, 2020;Alcalá-Vida et al, 2021). Histone acetylases and deacetylase also regulate proper NSC function through huntingtin expression regulation (Yildirim et al, 2019).…”
Section: Mitochondrial Physiology Autophagy and Epigenetics Interplay...mentioning
confidence: 99%
“…In this context, transcriptional reprogramming via stable epigenetic marks like histone modifications ( 56 ) or DNA methylation ( 23 ) is a plausible underlying molecular mechanism. Epigenetic dysregulation has been implicated in several neurodegenerative diseases including Huntington’s disease ( 57 ), Alzheimer’s disease ( 58 ), and MS ( 25 ). As a result, histone methyltransferases have become promising therapeutic targets in neurodegenerative diseases ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the binding of LSD1 enzyme to target genes, mediated by HOTAIR, has been shown to affect the repression of target genes by changing the methylation level of the histone H3 lysine 27 (H3K27) (Tsai et al, 2010). While, decreased acetylation of H3K27 showed an association with the downregulation of neuronal identity genes in the striatum of HD patients and mice (Achour et al, 2015;Alcalá-Vida et al, 2021). Also, an association is shown between aberrant DNA methylation levels correlated with aberrant expression of different lncRNAs with susceptibility to different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, exploration of the HD-associated epigenetic signatures using the slowly progressing knockin (KI) mouse model of HD, revealed that even before the onset of HD motor problems, age-related epigenetic remodeling and transcriptional alteration of neuronal and glial-specific genes are accelerated. This might suggest that the progressive HD striatal epigenetic signatures develop from the earliest stages of HD ( Alcalá-Vida et al, 2021 ).…”
Section: Dna Methylation Age Acceleration In Huntington’s Diseasementioning
confidence: 99%